Syntactic Analysis in WhatsApp Conversations Among Peers - Ummi Aisyah Siregar; Nabila Ramadani; Fariza Putri Ramadhani Siregar (Jurnal Hata Poda, 2025)
Sentence structure in WhatsApp conversations among peers is usually simple, brief, and tends to be informal, with frequent use of single sentences that are flexible and do not always follow standard grammar. Communication through WhatsApp prioritizes fluency, speed, and expressive intimacy over adherence to formal grammatical structures. This study uses a literature review method as the main technique for data collection. The data analysis technique in this study uses a qualitative approach focusing on the analysis of content and sentence structure comprehensively. Data is obtained from WhatsApp conversation transcripts arranged according to the conversation context, and then analyzed descriptively by identifying various forms of sentence structures according to syntactic theory. A qualitative analysis of the syntactic aspects in sentence structures in WhatsApp conversations among peers shows that the sentences used are generally short and incomplete. The use of elliptical sentences, which are sentences that omit elements such as the subject or predicate, is very common in these interactions. This phenomenon reflects a tendency to convey messages briefly and effectively, in line with the characteristics of digital communication that demand speed and efficiency in delivering information. The language style used in these conversations is casual and informal. Therefore, the results of this study confirm that sentence structures in WhatsApp conversations among peers are more flexible and functional compared to the formal sentence structures typically found in official or academic communication.